2020
DOI: 10.24093/awej/vol11no2.23
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Visual Vocabulary for ESL Students’ Vocabulary Learning

Abstract: Vocabulary is often neglected despite being one of the most crucial aspects of language acquisition. Due to the lack of emphasis on vocabulary learning, ESL students have issues in learning the English language effectively, which resulted in low-level language proficiency. Hence, this paper attempts to address this problem by introducing Visual Vocabulary to learn the target words. The main research question: How effective is the use of the Visual Vocabulary to learn vocabulary for Form Two learners? To invest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Visuals also help activate the learners' interest and motivation. They can also provide knowledge of the language context and a focused reference or stimulus [20]. Hence, visuals elements are crucial in supporting ESL and EFL learning efficiently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visuals also help activate the learners' interest and motivation. They can also provide knowledge of the language context and a focused reference or stimulus [20]. Hence, visuals elements are crucial in supporting ESL and EFL learning efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reading strategies, lack of motivation, and unavailability of good materials are also factors that negatively affect EFL learners during reading comprehension [18]. Some studies have also reported that most ESL and EFL learners experience difficulty because of their restricted word choice [18][19][20]. In addition, the lack of motivation among ESL and EFL learners to speak the target language is one of the reasons why students cannot speak the English language in the language classrooms.…”
Section: The Importance Of Non-textual Elementsmentioning
confidence: 99%
“…Moreover, vocabulary is the knowledge of words and word meanings By arising vocabulary or sufficient word collections, the students do not only get the meaning of words, but will be able to use and learn from the simple one, that is the daily life communication. An explanation tells that, the vocabulary knowledge is not something that can ever be fully mastered (Mohamad and Ariff, 2020); it is something that expands and deepens over the cause of a lifetime. It is stated out, because the language growth is always growing gradually.…”
Section: Vocabulary Understandingmentioning
confidence: 99%
“…This statement shows that vocabularies are the main attribute that contributes to language learning. Many studies agreed that obtaining vocabulary is the first step in acquiring language [23][24][25].…”
Section: Trends In Espmentioning
confidence: 99%